Domestic Rivalry and Export Performance: Theory and Evidence from International Airline Markets - Joseph A. Clougherty; Anming Zhang (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2008)
The much-studied relationship between domestic rivalry and export performance consists of those supporting a national-champion rationale, and those supporting a rivalry rationale. While the empirical literature generally supports the positive effects of domestic rivalry, the national-champion rationale actually rests on firmer theoretical ground. We address this inconsistency by providing a theoretical framework that illustrates three paths via which domestic rivalry translates into enhanced international exports. Furthermore, empirical tests on the world airline industry elicit the existence of one particular path - an enhanced firm performance effect - that connects domestic rivalry with improved international exports.
urn:nbn:de:bvb:19-epub-13327-6
Keywords: L52; L40; L93; 330